The visual resonances of a Harari Qur’ān: An 18th century Ethiopian manuscript and its Indian Ocean connections - Sana Mirza (Afriques)
Although not widely recognized as Harari, a Qur’ān manuscript in the Khalili Collection in London (QUR706) provides an opportunity to consider long-distance artistic circulations and encounters in the early modern Indian Ocean. Dated to 1162/1749, the Khalili Qur’ān can be linked with Mamluk and earlier Indian Qur’ān manuscripts through its illuminations and its use of biḥārī script, a type rarely seen outside of India. Later inscriptions in the Qur’ān record its eventual arrival in Zanzibar. The trans-regional visual resonances of the manuscript, and its later circulation, highlight the position not only of Harar as a regional artistic center within Ethiopia, but also that of the Horn of Africa within a broader Indian Ocean ecumene. Focusing on the Khalili Qur’ān, this essay will explore Harar’s nuanced engagement and selective participation in networks of artistic circulation and exchanges and their role in the formation of a Harari visual idiom within the burgeoning globalization of 18th-century Ethiopia.